The fragmentation of massive star-forming regions - Rodón, Javier Adrián (2009)
Since its discovery by E. Salpeter in 1955, the high-mass end of the Initial Mass Function (IMF) has been continuously tested, and its slope has not changed from the value -2.35 originally calculated by Salpeter, the "Salpeter value". Furthermore, it is found that this value is universal. It not only describes the mass distribution of stellar masses in the Milky Way but also in other galaxies. Stars form individually or in systems within molecular clouds, from local condensations of sizes on the order of ~0.01 pc, the so-called "dense cores". In the case of low-mass star-forming regions, it is found that the Core Mass Function (CMF) resembles the Salpeter IMF. However, in the case of massive star-forming (MSF) regions, the answer is not that clear. The first CMF for a MSF region was derived in 2004 by H. Beuther and P. Schilke for the MSF region IRAS19410+2336. They found that this CMF also resembled the Salpeter IMF. Since then, a few more CMFs for MSF regions have been derived, always with exponents comparable to Salpeter. This suggested that the CMF and the IMF are related in a one-to-one or nearly one-to-one relationship, and that the fragmentation processes within a molecular cloud would set the shape of the IMF at an early evolutionary stage ...